2015
DOI: 10.1002/lno.10111
|View full text |Cite
|
Sign up to set email alerts
|

Physical‐biological coupling of N2 fixation in the northwestern South China Sea coastal upwelling during summer

Abstract: Here, we present the first combined results of N2 fixation rates (15N2 assay), dissolved iron (dFe, < 0.2 μm), and primary production (PP) (14C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N2 fixation rate ranged between 0.1 nmol N L−1 d−1 and 5.6 nmol N L−1 d−1 (average 1.0 nmol N L−1 d−1, n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N2 fixation rate ranged betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
8
20
5
Order By: Relevance
“…Enhanced Trichodesmium blooms have been observed frequently in the tropical/subtropical Atlantic, western Pacific, and Indian Oceans (Parab & Matondkar, ; Villareal & Carpenter, ; Westberry & Siegel, ), which are located downwind of major global dust production areas (Saharan/Sahel, Gobi Deserts, and deserts bounding the Arabian Sea, respectively) (Jickells et al, ; Karl et al, ). Our present reported blooming density (5,445 trichomes L −1 ) are consistent with those previously reported in the SCS (2,797 trichomes L −1 ) (Zhang et al, ) and tropical central (15°N–7°S, 1 × 10 3 trichomes L −1 ) (Snow et al, ) and eastern North Atlantic (2,860 trichomes L −1 ) (Tyrrell et al, ), but are considerably lower than that observed in the Kuroshio (>2 × 10 4 trichomes L −1 ) (Shiozaki et al, ), central (>1 × 10 4 trichomes L −1 ) (Capone et al, ) and eastern (40.07 × 10 4 trichomes L −1 ) (Parab & Matondkar, ) Arabian Sea, western North Atlantic (20.62 × 10 3 trichomes L −1 ) (Carpenter et al, ), and Brazil Current in the South Atlantic (10.9 × 10 6 trichomes L −1 ) (Detoni et al, ). These findings are largely attributed to the higher terrestrial/riverine and atmospheric inputs of macronutrients and micronutrients in the ECS, Arabian Sea, and tropical/subtropical North Atlantic than in other seas, particularly with respect to the availability of Fe and P (Jickells et al, ; Karl et al, ; Rubin et al, ; Sañudo‐Wilhelmy et al, ; Snow et al, ; Sohm, Webb, & Capone, ).…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced Trichodesmium blooms have been observed frequently in the tropical/subtropical Atlantic, western Pacific, and Indian Oceans (Parab & Matondkar, ; Villareal & Carpenter, ; Westberry & Siegel, ), which are located downwind of major global dust production areas (Saharan/Sahel, Gobi Deserts, and deserts bounding the Arabian Sea, respectively) (Jickells et al, ; Karl et al, ). Our present reported blooming density (5,445 trichomes L −1 ) are consistent with those previously reported in the SCS (2,797 trichomes L −1 ) (Zhang et al, ) and tropical central (15°N–7°S, 1 × 10 3 trichomes L −1 ) (Snow et al, ) and eastern North Atlantic (2,860 trichomes L −1 ) (Tyrrell et al, ), but are considerably lower than that observed in the Kuroshio (>2 × 10 4 trichomes L −1 ) (Shiozaki et al, ), central (>1 × 10 4 trichomes L −1 ) (Capone et al, ) and eastern (40.07 × 10 4 trichomes L −1 ) (Parab & Matondkar, ) Arabian Sea, western North Atlantic (20.62 × 10 3 trichomes L −1 ) (Carpenter et al, ), and Brazil Current in the South Atlantic (10.9 × 10 6 trichomes L −1 ) (Detoni et al, ). These findings are largely attributed to the higher terrestrial/riverine and atmospheric inputs of macronutrients and micronutrients in the ECS, Arabian Sea, and tropical/subtropical North Atlantic than in other seas, particularly with respect to the availability of Fe and P (Jickells et al, ; Karl et al, ; Rubin et al, ; Sañudo‐Wilhelmy et al, ; Snow et al, ; Sohm, Webb, & Capone, ).…”
Section: Discussionsupporting
confidence: 93%
“…The nSCS basin showed low N 2 fixation activity. These rates were in the same order of magnitude as those measured under non-bloom conditions in the East China Sea, the southern Yellow Sea and the nSCS coastal upwelling 27,28 . The high N 2 fixation rates in the nSCS shelf were probably attributed to diazotrophic blooms in sampling stations.…”
Section: Resultssupporting
confidence: 73%
“…On the basis of a C: N = 6.6, N 2 fixation by the whole-water was calculated to contribute to 1.7% to 18.5% of the primary production in surface waters, suggesting that N 2 fixation plays a very important role in supporting surface phytoplankton N demand in some stations. Such values were exceeded the previous studies in the nSCS, and were comparable with N input by biological N 2 fixation in other oceans 27,28,56 . The variation of N 2 fixation rate by Trichodesmium was consistent with that of the standing crop of Trichodesmium .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Because colonies were easily missed during water‐sample collection due to the limited volume (~1 L) of sampled seawater and low colony densities (Jiang et al, ; Shiozaki, Takeda, et al, ), the present colonial trichomes might be underestimated. Nevertheless, this contribution was higher than those reported in the South China Sea (Zhang et al, ) and at station ALOHA (Letelier & Karl, ), but was lower than those (>70%) in the North Pacific subtropical gyre (Sohm, Subramaniam, et al, ) and North Atlantic (Carpenter et al, ). Particularly in the southeastern ECS, the colonial trichomes accounted for 68%, which was consistent with that (69%) reported in upstream Kuroshio during summer (Chen et al, ).…”
Section: Discussionmentioning
confidence: 58%